2017
DOI: 10.5603/ep.2017.0004
|View full text |Cite
|
Sign up to set email alerts
|

Remisja cukrzycy typu 2 po leczeniu bariatrycznym — porównanie różnych procedur

Abstract: Introduction: We aimed to assess the mid-term type 2 diabetes mellitus recovery patterns in morbidly obese patients by comparing some relevant physiological parameters of patients of bariatric surgery between two types of surgical procedures: mixed (roux-en-Y gastric bypass and biliopancreatic diversion) and restrictive (sleeve gastrectomy). Material and methods: This is a prospective and observational study of co-morbid, type 2 diabetes mellitus evolution in 49 morbidly obese patients: 37 underwent mixed surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Recently published results of a meta-analysis underline the hypothetical positive effects of bariatric procedures on the control of glucose metabolism and improvements of normoglycaemia in diabetic patients [86][87][88].…”
Section: Resultsmentioning
confidence: 99%
“…Recently published results of a meta-analysis underline the hypothetical positive effects of bariatric procedures on the control of glucose metabolism and improvements of normoglycaemia in diabetic patients [86][87][88].…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to other studies, they concluded that there was no difference in T2DM remission rates after the three procedures, and a substantial 80% of patients had remitted at a one-year follow-up. They mention that this finding could be because only morbidly obese (BMI >50.2kg/m 2 ) patients were included in their study, as opposed to other studies (which include patients with lower BMIs) that show a clear superiority of RYGB over other procedures [ 28 ]. This finding from the Fernández-Soto et al study can be compared with results from Behbehani et al, where participants had a BMI >50.3kg/m 2 and RYGB was still the dominant procedure for attaining remission.…”
Section: Reviewmentioning
confidence: 99%
“…III) [21]. Despite the high efficacy and safety of bariatric surgeries [22][23][24], they are still not a frequently chosen therapeutic option by patients and physicians, especially because of the limited availability of bariatric surgery centres. Taking these facts into account, pharmacotherapy becomes an important aspect of obesity treatment.…”
Section: Obesity Treatmentmentioning
confidence: 99%